Avoiding Chaotin Instability under PID Control of Plythylene Fluidized Bed Reactor (UNIPOL Procees) - Nayef Mohamed Ghasem; Mohamed Azlan Hussain (ASEAN Journal of Chemical Engineering, 2003)
Modeling investigation showed that static and dynamic bifurcation behavior covers wide regions of the design and operatin domain of the fluidized bed reactor for polythylene production. In some cases, if comes across that the optimum static state is unstable and surrounded by a periodic branch with large tempertature oscillations causing fomidably high termperature far above the melting point of the polymer. A proportional-derivative-integral controller has been investigated for the stabilization of these desirableunstable steady states and the characteristic of the closed loop control system are presented and discussed. Even under the PID control scheme it was observed that care should be taken dor selecting suitable control gain to avoid instability.